Management and Production of Banana Stem Chips as an Alternative Business and Local Product Innovation in Merjosari - S. Candra Hastuti; Windy Wahju Purnomo (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2026)
Merjosari Village, Malang City, boasts abundant natural resources in the form of banana plantations. After the fruit is harvested, banana stems ("gedebok") are often considered waste and underutilized, even though they have the potential to be processed into value-added products. This Community Service (PKM) activity aims to transform this organic waste into an innovative, high-value food product: banana stem chips. The activity method consists of practical training and mentoring focused on housewives in RW 08 RT 09, Joyo Asri, Merjosari. This training not only reduces organic waste but also aims to open new business opportunities and encourage local product innovation. The expected results are increased family income, increased productive activities of residents, and collectively strengthening the community economy through the development of Micro, Small, and Medium Enterprises (MSMEs) based on local potential. This activity will be implemented in May 2025.